1997
DOI: 10.1152/jappl.1997.82.5.1616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stochastic heterogeneity on lung impedance during acute bronchoconstriction: a model analysis

Abstract: In a previous study (J. H. T. Bates, A. M. Lauzon, G. S. Dechman, G. N. Makaym, and T. F. Schuessler. J. Appl. Physiol. 76: 616-626, 1994), we investigated the acute changes in isovolume lung mechanics immediately after a bolus injection of histamine. We found that dynamic resistance and elastance increased progressively in the 80-s period after injection, whereas the estimated tissue hysteresivity reached a stable plateau after approximately 25 s. In the present study, we developed a computer model of the lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 36 publications
6
103
1
Order By: Relevance
“…This neglects all of the heterogeneity among airways of different sizes and generations that is known to characterize the lung, and it makes numerous simplifying assumptions about the dynamics of ASM contraction and parenchymal mechanics (5). It also assumes a particularly simple mathematical form for the stiffness of the airway wall (35), which is certain to be a gross oversimplification of reality. Indeed, our laboratory recently showed that, even though this model accounts for much of the transient dynamics in R following a deep lung inflation in constricted mice (3), there appears to be significant effects due to tissue viscoelasticity in these dynamics for which the model does not account.…”
Section: Discussionmentioning
confidence: 99%
“…This neglects all of the heterogeneity among airways of different sizes and generations that is known to characterize the lung, and it makes numerous simplifying assumptions about the dynamics of ASM contraction and parenchymal mechanics (5). It also assumes a particularly simple mathematical form for the stiffness of the airway wall (35), which is certain to be a gross oversimplification of reality. Indeed, our laboratory recently showed that, even though this model accounts for much of the transient dynamics in R following a deep lung inflation in constricted mice (3), there appears to be significant effects due to tissue viscoelasticity in these dynamics for which the model does not account.…”
Section: Discussionmentioning
confidence: 99%
“…We adapted a recently developed model for the analysis of the time course of acinar flow and pressure during MV (21). The model is based on the branching network proposed for the human lungs by Horsfield et al (15), and it is a careful simplification of previously published computational models of lung mechanics in the frequency domain (14,30). Briefly, the Horsfield airway tree is an asymmetric bifurcating network with 35 orders.…”
Section: Methodsmentioning
confidence: 99%
“…Order 35 corresponds to the trachea. Therefore, the conducting airways are orders , whereas airway orders 1-7 represent the pulmonary acini (30). In our model, each airway is represented by a combination of laminar resistance and wall compliance (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This question has been addressed in two recent studies investigating the contribution of heterogeneity to the increase in pulmonary impedance in response to bronchoconstrictive agonists [23,24]. In both instances, the authors used the Horsfield asymmetric airway tree and computational models to determine lung resistance and elastance.…”
Section: Mathematical Models Of Airway Narrowingmentioning
confidence: 99%